The Effects of Different Reciting Styles of Quran on Emotions among University Students - Nayef, Eman Ghanem; Muhammad Nubli, Abdul Wahab (Human Resource Management Academic Research Society (HRMARS), 2018)
This study examined the effects of Quran recitation on the Heart Rate Variability (HRV) of 30 undergraduate students who study in University Malaysia Pahang (UMP). One of the important effects of the Quran on student learning and achievement is reflected in emotions. Emotions control the attention of students, influence their motivation to learn, modify their choice of learning strategies and affect their self-regulation of learning. Furthermore, emotions are part of student identity, and they affect personality development, psychological health and physical health. Repeated measures quasi experimental design method was conducted, thirty undergraduate students whom participated in the test were divided into two groups; good Quran reciters group and weak Quran reciters group, every student has been attending four sessions. In the first session, the reciter focused on Tajweed rules, the second session student focused on some stories in a certain Surah, third session focused on certain verses of heaven, hell and punishment in Quran, and last session focused on understanding the meaning of the Quran and at the end of this session the student reads text from a newspaper. The parameters of heart rate variability (HRV) were measured to examine the outcome. The results show a clear difference in HRV data between good and weak readers, good readers have control of their heart actions and reactions. Thus, the good reciter students have high score in HRV and better control of their heart function. The conclusion of this study showed that the Quran recitation significantly effects on the emotions of Quran reciters. Quran effects on psychological comfort for students by increased relaxation and reduced stress